2021
DOI: 10.3389/fceng.2021.632752
|View full text |Cite
|
Sign up to set email alerts
|

Sophorolipids Production from Oil Cake by Solid-State Fermentation. Inventory for Economic and Environmental Assessment

Abstract: Biosurfactants are being proposed as a substitute for surfactants in the framework of a circular economy strategy. Sophorolipids (SL) are a type of biosurfactant produced by yeast that can be produced through submerged or solid-state fermentation (SSF) processes. Even though sophorolipids are being produced at full scale, through submerged fermentations, environmental and technoeconomic information regarding its production through SSF is unavailable. An inventory of data necessary to perform preliminary econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…The biosurfactant extract with a capacity of dispersing 90% of oil drops in seawater was produced using two low-cost substrates (corn steep liquor and ground-nut oil refinery residue) in 20-L bioreactors obtaining a yield of 21 g L −1 at 144 h, similar to that obtained at lab-scale. Comparably, 37 ,used winterization oil cake and molasses as low-cost substrates for biosurfactant production in an SSF process with 22-L and 100-L reactors with S. bombicola , achieving a yield of 0.19 gSL gDM −1 and 0.14 gSL gDM −1 , respectively, showing the production adaptability that this microorganism presents. It should be highlighted that SSF is carried out using solid substrates where microorganisms grow in the absence of free water.…”
Section: Production Of Biosurfactantsmentioning
confidence: 99%
“…The biosurfactant extract with a capacity of dispersing 90% of oil drops in seawater was produced using two low-cost substrates (corn steep liquor and ground-nut oil refinery residue) in 20-L bioreactors obtaining a yield of 21 g L −1 at 144 h, similar to that obtained at lab-scale. Comparably, 37 ,used winterization oil cake and molasses as low-cost substrates for biosurfactant production in an SSF process with 22-L and 100-L reactors with S. bombicola , achieving a yield of 0.19 gSL gDM −1 and 0.14 gSL gDM −1 , respectively, showing the production adaptability that this microorganism presents. It should be highlighted that SSF is carried out using solid substrates where microorganisms grow in the absence of free water.…”
Section: Production Of Biosurfactantsmentioning
confidence: 99%
“…The base scenario was based on previous work performed at different scales, with reactor volumes of 500 mL [9], and 22 and 100 L [29]. These studies demonstrated the feasibility of the production of SL through SSF at bench and pilot-scale, using winterization oil cake (WOC) and molasses (MOL) as substrates, wheat straw (WS) as the support material to provide porosity and resistance to compaction, and S. bombicola ATCC 22214 (American Type Culture Collection, Manassas, VA, USA) as the SL-producing yeast.…”
Section: Base Scenariomentioning
confidence: 99%
“…Under these conditions, the productivity is 0.026 g SL/g dry matter d, and the obtained production yield is 0.72 g SL/g fat (corresponding to 0.26 g SL/g WOC). Based on the results obtained for 100 L reactors, we considered a scale-up factor and assumed to achieve 85% of the SL yield obtained in our previous works, as a conservative value in the simulation [29].…”
Section: Base Scenariomentioning
confidence: 99%
See 2 more Smart Citations